Empathy for the Depicted - Kyprianidou, Efi (My University, 2017)
Recently, a number of philosophers and neuroscientists have begun to explore the idea we may experience empathy for pictures. In this paper I explore the variety of ways in which we respond empathetically towards pictures. Empathy in response to pictures can refer either to the idea that the viewer empathizes with the depicted character’s emotional state, or that the viewer empathizes with depicted scenes, in the sense of responding towards a depicted scene’s expressed emotions. Regarding the latter, I question the idea that we can have a full-blown empathetic response to a scene that does not involve attributing emotions to a person, either depicted or hypothetical. I then explore responses to depicted characters, starting from a distinction between low-level motoric responses to pictures that afford an understanding of the viewer’s bodily involvement in attending pictures, and emotional or empathetic responses. It is argued that neural and embodied simulation processes prompt passive and immediate responses to depicted characters, that are not though empathetic. These responses may give rise to automatic, immediate and conscious responses that provide a minimal access to the depicted character’s perspective. Lastly, two main accounts of imaginative reconstruction or perspective shifting that have been proposed are examined as possible types of engagement with a depicted character.
Keywords: Empathy; Aesthetics; Perspective change